PELATIHAN TEKNIK PEMASARAN DIGITAL PADA MASYARAKAT DI DESA JAYABAKTI - Rizky Maulana Julian; Siti Asiah; Ria Marginingsih (Universitas Islam 45 Bekasi, 2023)
The purpose of implementing community service is to improve the quality of human resources in understanding digital marketing in the village of Jayabakti. The development of digital marketing is still not well understood by the public because of the lack of directors and training on digital marketing. The method of implementing community service applies socialization and training methods to advance marketing in the Jayabakti Village community. Implementation of community service is carried out with three activities (1) digital marketing outreach, (2) training in marketing techniques through digital media or social media, (3) marketing consulting. The results of community service activities are proven by the level of understanding of the community regarding digital marketing and MSME actors who have started using social media as product marketing.